(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This article is an analysis of the first novel written by British author Rebecca West, The Return of the Soldier (1918). Despite the popularity and high appreciation she enjoyed during her lifetime, Rebecca West simply disappeared from the modernist canon. Her first novel has very visible modernist traits, contemporary topic and interesting narration methods, and therefore truly deserves a new reading audience.